A pregnant woman with a giant bilateral parietal hemangiopericytoma underwent multiple surgeries and radiotherapy: a case report and literature review - Wu, Yingxi; Xue, Yafei; Wang, Xinqi; Li, Junting; Qu, Yan; Zhao, Tianzhi (Frontiers in Oncology, 2023)
Intracranial hemangiopericytoma is a rare invasive tumor originating from mesenchymal fibroblasts and is prone to local recurrence and distant metastasis. This study reports a case of a 27-year-old woman who presented with severe headache, nausea and vomiting for two weeks at thirty-three weeks of gestation. Cranial magnetic resonance imaging (MRI) demonstrated a giant lesion in the bilateral parietal lobe with a size of 5.12x9.19x6.03 cm and severe edema in the surrounding brain tissue. The patient underwent four operations and 3 gamma knife radiosurgery procedures and is recovering well now. The histopathology findings showed hemangiopericytoma and STAT6 and CD34 positivity after the first and second surgeries. Because of tumor progression, the patient received gamma knife radiosurgery at 1, 3, and 4 years after the first operation. Total tumor resection was achieved in the fourth surgery. Nevertheless, the patient showed malignant transformation to from low-grade to high-grade hemangiopericytoma.